М.О. Мірошниченко – один з двадцяти керівників навчального закладу - Боровик, А. (Сiверянський лiтопис, 2015)
Увазі читача пропонуються маловідомі сторінки історії Чернігівського інституту соціального виховання початку 30-х років ХХ ст. Мова йде про короткий період управління вузом М. О. Мірошниченком. Вниманию читателя предлагаются малоизвестные страницы истории Черниговского института социального воспитания начала 30-х годов ХХ ст. Речь идёт о кратком периоде управления вузом Н. А. Мирошниченком. During almost a century of activity in the history of T.H. Shevchenko Chernihiv National
Pedagogical University have been many changes in the organization of educational process,
in the formation of the material base of the institution and in its structure. Its leaders also
changed. In this article we are talking about the brief period of management of the Institute
by Miroshnychenko Mykola Oleksandrovych. His work as head of the educational institution
previously has not been reported in the historical literature.